RISK FACTORS OF BRONCHOPULMONARY DYSPLASIA DEVELOPMENT IN NEONATES WITH VERY LOW AND EXTREMELY LOW BIRTH WEIGHT - O. V. Lebedeva (Union of pediatricians of Russia, 2014)
The study was aimed at investigating the perinatal factors and levels of pro- (IL1α, IL6) and anti-inflammatory (IL1RA, IL10) cytokines in order to clarify their role in immune pathogenesis and prediction of bronchopulmonary dysplasia (BPD). Patients and methods: the prospective study involved 194 neonates with birth weight of 600-1,500 g and gestational age of 25‑32 weeks. The primary perinatal risk factors and their role in BPD development in children with very low (VLBW) and extremely low (ELBW) birth weight were analyzed. A special screening program consisted in determining serum levels of IL1α, IL1RA, IL6 and IL10 in the 3rd-5th and the 7th-10th day of life with enzyme-linked immunosorbent assay using test systems manufactured by Cytokine, LLC. 40 neonates with and 40 neonates without BPD underwent immunological examination. The BPD incidence was 46.6% in neonates with ELBW and 10.5% in children with VLBW. BPD risk factors for BPD in VLBW neonates were low APGAR score in the 1st minute (p = 0.02), severe respiratory distress syndrome (RDS; p < 0.001) and pneumonia (p < 0.001). Gestational age under 27 weeks (p = 0.001) had the primary role in children with ELBW; other risk factors included body weight (p = 0.02), low APGAR score in the 1st (p = 0.03) and the 5th minutes (p = 0.002), severe RDS (p < 0.001) and pneumonia development (p < 0.001). According to the comparative evaluation of prognostic significance of the level of pro-and anti-inflammatory cytokines in infants with BPD, IL1RA has the highest information value when its level > 670 pg/ml and IL6 ≥ 25 pg/ml.